KINERJA AUDITOR PEREMPUAN DITINJAU DARI KOMPLEKSITAS TUGAS DAN KOMITMEN ORGANISASI - Sri Hastuti; Rina Moestika; Tamadoy Thamrin (Behavioral Accounting Journal, 2018)
This research is a form of quantitative research to produce a model of performance improvement of auditors by conducting proof of Task Complexity variable, as well as Orgasization Commitment with expected indicator is the improvement of professionalism and decreasing of cases of code violation. The sample used was 133 junior auditors in Public Accounting Firm registered in IAPI East Java Compartment spread in 3 cities namely Surabaya, Sidoarjo and Malang. The research instrument is a questionnaire distributed directly to the respondents who were sampled in the study. By using Partial Least Square testing, the resulting model that the complexity of the task has a significant positive effect on audit performance, organizational commitment has no effect on audit performance.